[Translated article] Hip fractures in Spain. How are we? Systematic review and meta-analysis of the published registries - J.H. Núñez; F. Moreira; M. Surroca; J. Martínez-Peña; M.J. Jiménez-Jiménez; B. Ocrospoma-Flores; P. Castillón; E. Guerra-Farfán (Revista Española de Cirugía Ortopédica y Traumatología)
Objective: Spain is expected to be the country with the highest life expectancy in the coming years. In this context, it is important to improve the care of hip fractures. The objective of this work was to describe the results of the registries published on hip fractures in Spain. Material and methods: Systematic review and meta-analysis of the records published on hip fractures in Spain, the last 10 years. The characteristics of the study, characteristics of the patients, of the fractures, the type of surgery, as well as morbidity and mortality were analyzed. Results: A total of 55,680 patients with a mean age of 84.6 years were analyzed, of whom 75% were women. Extracapsular fractures were the most frequent (58%). It was found that conservative treatment was applied in an average of 3% of cases. The average surgical delay was 64.7 h, with a mean percentage of patients operated on within 24 h at 18%, and within 48 h at 40%. A mean hospitalization time of 10.7 days was found. Delirium was found to be the most frequent postoperative complication (42%). The mean transfusion rate was 36%. Mean in-hospital mortality at one month and one year was 4%, 5% and 18%, respectively. Conclusions: Less than half of patients with a hip fracture undergo surgery within 48 h, despite being recommended by the majority of clinical practice guidelines. Delirium is the most frequently reported postoperative complication, and one in every 5 patients will die within a year after a hip fracture. Standardizing the management of hip fractures at the state level could improve healthcare quality and facilitate the establishment of common criteria for good clinical practice. Resumen: Introducción: Se prevé que España sea el país con mayor esperanza de vida en los próximos años. En este contexto, es importante mejorar la atención de las fracturas de cadera. El objetivo de este trabajo fue describir los resultados de los registros publicados sobre fracturas de cadera en España. Material y métodos: Revisión sistemática y metaanálisis de los registros publicados sobre fracturas de cadera en España en los últimos 10 años. Se analizaron las características del estudio, las características de los pacientes, de las fracturas, del tipo de cirugía, así como la morbimortalidad. Resultados: Se analizó 55.680 pacientes con una edad media de 84,6 años, de los cuales el 75% eran mujeres. Las fracturas extracapsulares fueron las más frecuentes (58%). Se halló que el tratamiento conservador se aplicó en un promedio del 3% de los casos. La demora quirúrgica media fue de 64,7 h, mientras que el porcentaje medio de pacientes operados en menos de 24 h fue del 18% y el de menos de 48 h fue del 40%. Se halló un tiempo de hospitalización medio de 10,7 días. Se encontró al delirium como la complicación postoperatoria más frecuente (42%). El porcentaje de transfusión medio fue del 36%. La mortalidad media intrahospitalaria, al mes y al año fue del 4, 5 y 18%, respectivamente. Conclusiones: Menos de la mitad de loa pacientes con fractura de cadera son operados en menos de 48 h a pesar de ser recomendado por la mayoría de guías de práctica clínica. El delirium es la complicación postoperatoria más frecuente reportada y uno de cada 5 pacientes morirá al año, tras la fractura de cadera. Homogeneizar el manejo de la fractura de cadera a nivel estatal podría mejorar la calidad asistencial y permitiría la creación de criterios comunes de buena práctica clínica.